The hydrated lime dissolution kinetics in acid mine drainage neutralization - Mgabhi, Senzo Mntukhona (Department of Chemical Engineering, 2021)
Hydrated lime, Ca(OH)₂, has been rediscovered as an environmentally sustainable product, which could be of help in the remediation of acid mine drainage (AMD), especially in the AMD neutralization process. This is due to its ease of acquisition, affordable price and unique versatile properties such as reactivity and neutralization efficiency. AMD is an acidic wastewater containing high concentrations of sulphates and dissolved heavy metals mainly ferrous iron. The dissolution of Ca(OH)₂ in aqueous solution is complex, which make its kinetics in AMD neutralization difficult to understand. The aim of this study was therefore to understand the Ca(OH)₂ kinetics in simplified solutions such as de-ionized water and CH₃COOH. The neutralization process is an acid-base reaction; therefore, pH was used as a critical parameter in determining Ca(OH)₂ dissolution rate. The determination of the dissolution rate was attempted in two ways – measurement of dissolved calcium and determining change of particle size distribution. There were two methods of determining calcium assays investigated, that is EDTA-EBT titration method and OCPC spectrophotometric method. Both methods worked successfully for a Ca(OH)₂-H₂O system. The EDTA-EBT titration method worked better even at higher concentrations of calcium (up to 100 ppm) while the complexometric spectrophotometric method was consistent with Beer-Lambert Law for a narrow calcium concentration range of 1 to 2 ppm, when a small amount of magnesium was introduced. However, both methods failed in the presence of appreciable quantities of magnesium, sulphates and ferric ion. The investigation for particle characterization found that image analysis of SEM images was a better particle-size characterization option than laser diffraction measurement, which tended to cause blinding of the instrument window, but still yielded only qualitative results. There were four reactor configurations used, that is batch reactor for determining the effect of the hydrodynamics (stirring rate and powder addition) and three types of slurry CSTRs. The jacketed chemostat was found to be the optimal reactor configuration while the other two were used as base cases. The Ca(OH)₂ dissolution rate in de-ionized water decreased from 4.0×10⁻⁵ to 1.6×10⁻⁵ mol‧L⁻¹‧s⁻¹ when the temperature was increased from 26 °C to 42 °C. Correspondingly, the pH decreased with Ca(OH)₂ dissolution rate from 11.89 to 11.6. The dissolution rate expression was first order and consistent with the Nernst-Brunner Equation, with the dissolution rate constant of 2.34×10⁻³ s⁻¹ and the activation energy of 18.1 kJ mol ⁻¹ respectively. The overall Ca(OH)₂ dissolution rate in CH₃COOH solution decreased from 2.6×10⁻⁴ to 1.7×10⁻⁴ mol‧L⁻¹‧s⁻¹ when the temperature was increased from 25 °C to 44 °C. At constant ambient temperature (22°C), the Ca(OH)₂ dissolution rate increased with the decrease in pH from 12.1 to 4.38, then decreased with the decrease in pH from 4.38 to 3.5. Using pH to correlate dissolved calcium data and then to determine the rate of reaction, it was found that the dissolution rate is zeroth-order to hydrogen proton and first-order with respect to calcium concentration with the dissolution rate constant of 1.2×10⁻² s⁻¹ and the activation energy of 5.7kJ mol ⁻¹ respectively. These results confirmed that the dissolution of Ca(OH)₂ in DI water and the acetic acid solution is complex. The lower values of the activation energies (5.7 – 18.1 kJ mol ⁻¹), signifies that the kinetics of the Ca(OH)₂ dissolution are mass transfer controlled. Furthermore, these results were confirmed by the weak dependence of the dissolution rate to temperature. However, it was found that slurry CSTR is an efficient reactor system to study the effect of pH on the kinetics of hydrated lime at steady-state conditions.